Unpleasant emotions and associated factors during the COVID-19 pandemic in a university - Jana A. Mejía Toiber; Marco A. Escobar Acevedo; Ana María Cuéllar Castilla; Alejandro Gutiérrez González; Rodrigo Puga Castro (Nova Scientia, 2024)
The COVID-19 pandemic dramatically impacted Mexico, leading to the closure of educational institutions nationwide. Two years into the pandemic, schools, including the Technological University of Querétaro, were officially reopened. We surveyed the university community to evaluate the prevalence of unpleasant emotions. We gather data on demographics, social connections, psychological factors, and significant lifestyle changes attributed to the pandemic. Our analysis, based on a multivariable logistic regression, included responses from 2,616 participants. We identified an 8-24% prevalence rate for unpleasant emotions within our sample. Exhaustion, boredom, and frustration were the most intensely experienced emotions. The analysis revealed several risk factors for heightened unpleasant emotions: being a student (odds ratio [OR] = 1.85), younger age (OR = 2.91-3.00), poly-drug use (OR = 1.21-6.23), and increased substance consumption attributable to pandemic stress (OR = 3.32). Additionally, gender differences were observed, with female participants reporting higher levels of unpleasant emotions (OR = 1.18). Other significant factors included being single (OR = 1.61), experiencing social isolation (OR = 12.07), psychophysiological changes (OR = 6.59-174), and suicidal ideation (OR = 33.25). Our findings indicate a broad variation in the prevalence of unpleasant emotions among the university community, influenced by a range of demographic and psychosocial factors.